2004
DOI: 10.1111/j.1460-9568.2004.03759.x
|View full text |Cite
|
Sign up to set email alerts
|

Putative NMDA receptors in Hydra: a biochemical and functional study

Abstract: The feeding behaviour of the freshwater polyp Hydra vulgaris (Cnidaria, Hydrozoa) is modulated by a number of molecules acting as neurotransmitters in other nervous systems. Here we present biochemical and functional evidence of the occurrence of putative NMDA receptors in Hydra tissues. Saturation experiments showed the presence of one population of binding sites with nanomolar affinity and low capacity for [3H]MK-801. Before equilibrium, [3H]MK-801 binding was increased by the agonists glutamate and glycine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 43 publications
(55 reference statements)
1
29
0
Order By: Relevance
“…We would like to stress that the lingering controversy over the universality of the role of NMDA receptors as a key factor in learning and memory across different animal phyla, as well as over evolutionary aspects of functions for NMDA receptors (e.g., Wu, 2002;Rose et al, 2003) is primarily due to insufficient comparative data-especially data from basal metazoa (e.g., Pierobon et al, 2004;Scappaticci et al, 2004). Molecular and functional characterization of nonvertebrate homologs of these receptors would probably reveal novel regulatory mechanisms and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to stress that the lingering controversy over the universality of the role of NMDA receptors as a key factor in learning and memory across different animal phyla, as well as over evolutionary aspects of functions for NMDA receptors (e.g., Wu, 2002;Rose et al, 2003) is primarily due to insufficient comparative data-especially data from basal metazoa (e.g., Pierobon et al, 2004;Scappaticci et al, 2004). Molecular and functional characterization of nonvertebrate homologs of these receptors would probably reveal novel regulatory mechanisms and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We reported the identification and characterisation of the first invertebrate glycine receptor, whose biochemical and pharmacological properties also compare with those of vertebrate GlyRs (Pierobon et al, 2001). Saturation experiments revealed the existence of one population of binding sites for (Mothet et al, 2000).…”
Section: Inhibitory Transmitters and Receptors: Gaba And Glycinementioning
confidence: 99%
“…Following the discovery of strychnine-insensitive glycine binding sites in Hydra (Pierobon et al, 2001;see below), saturation experiments showed the presence of one population of binding sites with nanomolar affinity and low capacity for […”
Section: Excitatory Transmitters and Receptors: Glutamatementioning
confidence: 99%
See 1 more Smart Citation
“…Upon stimulation this cnidocil leads to the external discharge of an intracellular venom capsule (the nematocyst or cnidocyst), involved in the prey capture. Despite the simplicity of its nervous system, organized as a mesh-like network of neurons extending throughout the animal, the complexity of the mechanisms underlying neurotransmission resemble those of higher vertebrates, including both classical and peptidergic neurotransmitters (Pierobon et al, 2001;Pierobon et al, 2004). This makes Hydra an ideal system to study the behavioural response of a whole animal to an external stimuli, i.e.…”
Section: Hydra Vulgaris: An Ancient Model Systemmentioning
confidence: 99%